Tissue factor‐loaded collagen/alginate hydrogel beads as a hemostatic agent. Issue 8 (23rd December 2020) - Liu, Chengkun; Shi, Zhuang; Sun, Haiyan; Zhao, Lili; Wang, Xiaoqiang; Huang, Fang
Abstract: Uncontrolled hemorrhage accounts for a significant proportion of annual mortality worldwide. The development of bioinspired hemostatic composites can effectively reduce hemorrhage and related deaths. This work aims to develop an efficient hemostatic agent by incorporating tissue factor (TF) integrated liposomes and collagen, which are capable of augmenting different inherent hemostatic mechanisms, into hemostasis‐stimulating alginate matrix. The composite of TF, collagen and alginate (TCA) was made into hydrogel beads with a diameter range of 2.5–3.5 mm, followed by electron microscopy, infrared spectroscopy, rheological, and swelling characterization to confirm its composition and hydrogel nature. When the TCA beads were introduced into simulated body fluid, a controlled release of the loaded TF‐liposomes was observed, which also accelerated with the increase of temperature, obtaining intact free proteoliposomes as demonstrated by fluorescence measurement. It is further seen that TCA beads induced the coagulation of whole rabbit blood in about 4.5 min, as compared to ~14.4 min for the control with only recalcified blood. The lipidated TF, collagen and alginate in TCA beads showed a positive synergistic effect on coagulation, while among them a decreasing procoagulant effect was observed. Finally, we demonstrated by a live/dead cell assay that TCA particles had undetectable cytotoxicity. Thus, the TCA hydrogel macrobeads may offer a potential platform for the development of potent hemostatic agents.